Raised bed in a private garden in Yellowknife, NWT - Campbell, Sandy (2015)
Raised beds are common in Yellowknife, where there is little topsoil in which to make a garden. In this bed there are several flowers, herbs and vegetables including: marigolds, pansies, parsley, and chives (in bloom).